2015
DOI: 10.1159/000374053
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Low Intensity Physical Exercise Attenuates Heart Failure Development in Aging Spontaneously Hypertensive Rats

Abstract: Background: Physical exercise is a strategy to control hypertension and attenuate pressure overload-induced cardiac remodeling. The influence of exercise on cardiac remodeling during uncontrolled hypertension is not established. We evaluated the effects of a long-term low intensity aerobic exercise protocol on heart failure (HF) development and cardiac remodeling in aging spontaneously hypertensive rats (SHR). Methods: Sixteen month old SHR (n=50) and normotensive Wistar-Kyoto (WKY, n=35) rats were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(97 citation statements)
references
References 59 publications
(77 reference statements)
4
82
2
7
Order By: Relevance
“…Sections (5 µm thick) were stained with hematoxylin–eosin and collagen-specific stain picrosirius red (Sirius red F3BA in aqueous saturated picric acid) [46]. In at least 50 myocytes from each LV, where the nucleus could clearly be identified, the smallest transverse diameters were measured [47]. On average, 20 microscopic fields were used to quantify interstitial collagen fraction.…”
Section: Methodsmentioning
confidence: 99%
“…Sections (5 µm thick) were stained with hematoxylin–eosin and collagen-specific stain picrosirius red (Sirius red F3BA in aqueous saturated picric acid) [46]. In at least 50 myocytes from each LV, where the nucleus could clearly be identified, the smallest transverse diameters were measured [47]. On average, 20 microscopic fields were used to quantify interstitial collagen fraction.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the body surface of the individual participant may affect the lumen diameters of the coronary artery, and this could be easily determined if the coronary artery diameters were adjusted for body surface area. In addition, many therapies such as medications and kinesitherapy may affect the diameters of the coronary arteries and cardiac function [24, 25], and it would be optimal if we had obtained the data regarding the medications regularly taken by the included participants. Subsequent adjustment for medication use might minimize the potential confounding effect from the treatment.…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, it has been found that cardiac function varies with age in SHR rats [28,29], and the reason we chose 36-week-old SHR rats in our study is that the cardiac functions in SHR rats at this age simulated those of elderly hypertensive patients, i.e., chronic hypertension in this age group of patients has led to left ventricular hypertrophy and diastolic dysfunction [30,31].The blood pressure of SHR rats starts to rise at 6-8 weeks after birth; compensatory ventricular hypertrophy starts to develop at 16-18 weeks after birth; diastolic dysfunction begins to appear at about 36 weeks after birth, while systolic function remains in the normal range; and decompensated ventricular hypertrophy started to develop at 70 weeks after birth, with significant dilation of the ventricular cavity and significant decrease of systolic and diastolic function.…”
Section: Discussionmentioning
confidence: 95%